PEMANFAATAN PERANGKAT BERGERAK SEBAGAI MEDIA BELAJAR UNTUK PEROLEHAN BELAJAR ALGORITMA PEMOGRAMAN - Alexius Harnoto Trilaksono; M. Syukri; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research is an utilization research that have purposes to design a learning plan that can be easily accessible for all types of mobile devices, implements mobile devices, increases the acquisition of learning algorithms and programming and overcomes obstacles through the use of mobile devices as learning media. The method used in this study is a qualitative approach. Data collection techniques that will test the use of mobile devices include: observation, interview and documentation study. The subjects of this research are the students of Saint Paul Senior High School (10th grade). To start use the mobile media by making learning plans and making prototypes, prescribing learning tasks and message design. The next step is to create a story board, then continue using the product. Based on the research results of learning media applications with mobile devices can improve the acquisition of learning algorithms and programming. The other researchers can developed this media with other material or concepts.Keywords: Mobile Devices, Learning Media, Utilization